A fronte della potenza reale e simbolica del virus: la postura critica del ricercatore sociale tra persona e soggetto - Abruzzese, Alberto (Mediascapes Journal, 2020)
The aim of this article is to think about the inescapable relationship between our human condition and the scientific research that we carry out. It forces us into the present dramatic viral conjuncture of fear and pain. If we are really experiencing a dramatic "interval" in Western history, in modern subjectivity, it is a question of occupying it in order to rethink our "what to do" as researcher and teacher.